Calculation method for equivalent model of AC filters in HVDC transmission system. Issue 16 (7th January 2019) - Wentao, Lv; Zeyu, Xu; Chaoliang, Wang; Chen, Shen; Daozhuo, Jiang
Abstract : AC filter is an important part of HVDC system, which can restrain the AC‐side harmonics effectively and compensate for the reactive power consumed by converter station. Due to the harmonic characters of converter, double‐tuned filter and triple‐tuned filter are widely used in HVDC system. There is no model of double‐tuned filter or triple‐tuned filter in the common simulation software such as ETAP and DIgSILENT, which brought some difficulties to the simulation of HVDC especially harmonic analysis. To solve this problem, the accurate and simplified calculation method for equivalent models which instead double‐tuned filter and triple‐tuned filter by two parallel single‐tuned filters or three parallel single‐tuned filters are proposed. Furthermore, the accurate formulas and simplified formulas are given which can convert the parameters of double‐tuned filter or triple‐tuned filter to the parameters of parallel single‐tuned filters. Taking into account of the complexity of the accurate formulas, the resonant frequencies of double‐tuned filter and triple‐tuned filter are considered in the simplified formulas, which simplified the computational complexity. Finally, the feasibility of the equating method and the validity of parameters calculation method are verified.